Heat transfer and flowfriction behaviors in a channel with multiple 30° V-ribs - Khanoknaiyakarn, C.; Jedsadaratanachai, W.; Promvonge, P. (My University, 2014)
The paper presents an experimental study on heat transfer and flow friction characteristics in a rectangular channel fitted with periodically rectangular V-ribs. The multiple V-rib turbulators are tested in the channel having an aspect ratio (width to height ratio), AR=10 and height, H= 30 mm, with three rib-to-channel height ratios (e/H=0.2, 0.3, and 0.4), two rib-pitch to channel-height ratios (PR=P1/H= 3 and 4) and a single attack angle (α=30°). The upper plate of channel is uniformly heated at a constant heat-flux. The experiment has been conducted by varying airflow velocity in order to obtain the Reynolds number range from 5000 to 24,000. The experimental results show a significant effect of the presence of the ribs on the heat transfer rate and pressure drop over the smooth channel. The measured data indicates that the V-rib turbulators with e/H = 0.4 and PR =3 yields the highest heat transfer rate and friction loss. All the V-rib turbulators perform much higher than the smooth channel with no rib. © 2014 Asian Institute of Technology.
Keywords: Aspect ratio; Behaviors; Friction; Heat transfer; V-rib turbulators